Community Dependence on Lore Lindu National Park and Limited Production Forest in Kapiroe Village, Palolo Sub-district, Sigi Regency - Sari, Yudya Kurnia; Golar, Golar; Maiwa, Arman; Alam, Andi Sahri; Pribadi, Hendra; Rahman, Abdul (Cita konsultindo, 2025)
Dependence on forests is a condition in which humans are highly dependent on forests to support their livelihoods. Forests provide various natural resources. This study aims to determine the extent of community dependence on limited production forests and Lore Lindu National Park, as well as the factors that influence it. The research sample consisted of 58 people in Kapiroe Village, selected using the simple random sampling (SRS) methodology. Data were analysed using the Likert scale method. The dependence of the community in Kapiroe Village shows that 34.29% of the community's income comes from activities and utilisation in the TNLL area, while 65.7% comes from the HPT area. This finding confirms that the community of Kapiroe Village is highly dependent on limited production forests as their main source of livelihood. This high level of dependence highlights the role of the area in supporting the local economy, far exceeding the contribution of conservation areas such as TNLL.